ANALISIS PUTUSAN HAKIM TERHADAP PELAKU TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH APARAT PENEGAK HUKUM (Studi Putusan No : 10/Pid.Sus-tpk/2021/PT DKI) - Guslihan, Riza Aldia; Subaidi, Joelman; afrizal, teuku yudi (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
Corruption is an extraordinary crime and has a very wide impact because it will damage the country's economy. In the case of Prosecutor PSM in decision Number 10/Pid.Sus-tpk/2021/PT DKI, the sentence given by the judge does not reflect a sense of justice for the community, as the punishment is too lenient considering that the perpetrator is a law enforcement officer. Therefore, this research needs to be conducted to understand the criminal accountability of the perpetrator carried out by law enforcement officers and the judge's considerations in cases of corruption committed by law enforcement officers. The research method used in this study is normative juridical, utilizing primary, secondary, and tertiary legal sources, with the legal material collection techniques being library study and document study. Based on the law in Indonesia, Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 on the Eradication of Corruption Crimes aims to provide a deterrent effect to corruptors and prevent the occurrence of corruption.